Implementasi Pendidikan Adab (Ta’dib) sebagai Upaya Pembentukan Insan Kamil di Jenjang Dasar - Asalin Musoffa Sa’ad; Zaeni Dahlan (STAI Al-Hamidiyah Jakarta, 2025)
This research addresses the critical need for character education (ta'dib) in the modern Indonesian educational context, which often prioritizes technological advancement over moral development. PADI Elementary School, which adopts a pesantren (Islamic boarding school) system, serves as a case study for implementing such values. This study aims to describe the implementation, obstacles, and solutions of character education (ta'dib) at PADI Elementary School in its effort to shape students into Insan Kamil (complete/perfect human beings). The research employs a qualitative approach, utilizing observation and interviews with the school principal and a fifth-grade homeroom teacher to collect data. The implementation of character education is conducted effectively through several methods: (1) Special subjects like